Integrasi Agama dan Sains dalam Sistem Pendidikan Model Kuttab - Riduwan, Riduwan; Mahmud, Amir (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2023)
With the rise of curriculum-based religious education which is guided by memorization and mastery of reading and studying the Koran in elementary age children, education today is only oriented towards diplomas and tactical-mechanical abilities. Education during the time of the Prophet apart from teaching the ability to write and study the Koran also taught Adab and Faith, something that is rarely found in education today. However, along with developments in the era of the Prophet's era, education which was realized in the Kuttab education system was not enough to answer the challenges of the times, therefore Kuttab education must also be adaptive by integrating religious education in Kuttab with general knowledge content, or in other words, integrating religion and science. This research aims to describe the Kuttab model Islamic Education System, understand the integration between science and religion, and determine the qualifications of Al Fatih Malang kuttab model Islamic education graduates. This research uses a qualitative case study type approach. The results of this research show an integrative learning model in religious education. The Iman morafaqot curriculum in discussing science can be combined thematically with Al-Qur'an learning (Tadabbur), and mufarroqot in Al-Qur'an learning which is integrated with scientific observations. Kuttab Al Fatih Malang applies the relationship between science and religion with the principles of faith and the Koran. Implementation of the relationship between science and religion takes the form of habituation, namely the habituation of the muroja'ah of the Qur'an, and the implementation of 3S (Greetings, Smiles, Greetings).